24-chromosome PCR for aneuploidy screening. Issue 3 (June 2015) - Werner, Marie D.; Scott, Richard T.; Treff, Nathan R.
Abstract : Purpose of review: The purpose of this study is to describe the many advantages of PCR-based comprehensive chromosome screening (CCS) methodologies and the importance of extensive preclinical validation. Recent findings: The rigorous preclinical validation of quantitative real-time (q)PCR-based CCS involved an initial validation on cell lines, followed by a blinded evaluation on embryos. Comparison with alternative platforms and a prospective randomized clinical trial demonstrate superior precision and improved sustained implantation and delivery rates. Preclinical validation of targeted PCR-based next-generation sequencing (NGS) has also demonstrated consistency in positive controls, equivalent accuracy to commonly used techniques, high resolution, increased throughput, the simultaneous detection of single gene disorders and triploidy, and the potential to decrease costs. Prospective randomized controlled trials are ongoing to validate this technique for clinical use. Summary: CCS using PCR-based methodology improves implantation and delivery rates and allows for fresh embryo transfers. Other platforms are available to select euploid embryos; however, there are meaningful differences between techniques. PCR-based NGS technology may further enhance the utility of CCS for patients with infertility.